La capacidad del Congreso de los Diputados español para impulsar la incorporación del enfoque de Coherencia de Políticas para el Desarrollo (CPD) - Pérez-González, J.; Segovia-Moreno, M. (Revista Iberoamericana de Estudios de Desarrollo)
The international community has approved the 2030 Agenda for Sustainable Development as a common roadmap to face the global challenges of poverty, inequity and the sustainable management of the planet’s natural resources. For this Agenda to succeed, all countries must adopt the Policy Coherence for Development (PCD) approach as the guiding and crosscutting principle of all domestic and foreign policies during the next 15 years. National parliaments are going to be key players to urge Governments to make the ambitious and long-term commitments that the 2030 Agenda requires. Proyecto Avizor —a Spanish Parliament Monitoring Organization (PMO)— has monitored the activity of the Spanish Parliament during the 2011-2016 period, analyzing the contribution that the parliamentarian activity has had to promote the Government’s commitment in the fight against global poverty, inequality and in favor of sustainable development and human rights. With the information provided by Proyecto Avizor, this article has aimed to find if, in the current Spanish political context, the political initiatives that will be needed to fulfill the 2030 Agenda’s goals, face extra obstacles and burdens during their approval procedures compared withthe rest of initiatives. The results of the analysis show that the inclusion of the PCD approach in a political initiative decreases its chances of being successfully processed at the Parliament. On the other hand, the analysis has found no evidences that a stronger presence of the PCD approach in the political mandates approved by theParliament hampers its chances of being accomplished by the Government.Being solidarity one of the values on which the European Union is founded, the European regional framework becomes the most suitable level to increase the effectiveness of European aid, assuming responsibility for coordination and management of policy coherence.